LEMMATIC INFLUENCE ON VOCABULARY ACQUISITION AMONG L3 ENGLISH LANGUAGE LEARNERS IN TANZANIA - Kaoo, Lydia; Upor, Rose Acen (Indonesian Journal of Applied Linguistics, 2021)
This paper investigates cross-linguistic influence (CLI) on the acquisition of English vocabulary by third language (L3) learners in Tanzania. Specifically, the study aims to establish how lemmatic CLI from L1 and L2 influences L3 in a multilingual rural context where L1 is a dominant ethnic community language (L1=Haya, L2=Swahili, L3=English). Fourty students whose L1 was Haya participated in the study. They performed three language tasks i.e., word association task (WAT), letter writing task (LWT), and wordless picture narration (WPN). Using the Parasitic model of L3 vocabulary acquisition (Hall Ecke, 2003), the study found evidence of lemmatic transfer from background languages at form, frame and concept levels. More significantly, the L2 played instrumental and facilitative roles, both strategically and spontaneously, in influencing L3 vocabulary acquisition relative to the L1.Â  Into the bargain, the results show that the L2 is the predominant source language for lemmatic influence on L3 English and was modulated by proficiency and exposure. The study confirms that L3 learners reduce CLI as they increase L3 proficiency and that L2 acts as a filter for L2 features in L3.